Association Study between Folate Pathway Gene Single Nucleotide Polymorphisms and Gastric Cancer in Koreans - Jae-Young Yoo; Sook-Young Kim; Jung-Ah Hwang; Seung-Hyun Hong; Aesun Shin; Il Ju Choi; Yeon-Su Lee (Genomics & Informatics)
Gastric cancer is ranked as the most common cancer in Koreans. A recent molecular biological study about the folate pathway gene revealed the correlation with a couple of cancer types. In the folate pathway, several genes are involved, including methylenetetrahydrofolate reductase (MTHFR), methyltetrahydrofolate-homocysteine methyltransferase reductase (MTRR), and methyltetrahydrofolate-homocysteine methyltransferase (MTR). The MTHFR gene has been reported several times for the correlation with gastric cancer risk. However, the association of the MTRR or MTR gene has not been reported to date. In this study, we investigated the association between the single nucleotide polymorphisms (SNPs) of the MTHFR, MTRR, and MTR genes and the risk of gastric cancer in Koreans. To identify the genetic association with gastric cancer, we selected 17 SNPs sites in folate pathway-associated genes of MTHFR, MTR, and MTRR and tested in 1,261 gastric cancer patients and 375 healthy controls. By genotype analysis, estimating odds ratios and 95% confidence intervals (CI), rs1801394 in the MTRR gene showed increased risk for gastric cacner, with statistical significance both in the codominant model (odds ratio [OR], 1.39; 95% CI, 1.04 to 1.85) and dominant model (OR, 1.34; 95% CI, 1.02 to 1.75). Especially, in the obese group (body mass index ≥ 25 kg/m2), the codominant (OR, 9.08; 95% CI, 1.01 to 94.59) and recessive model (OR, 3.72; 95% CI, 0.92 to 16.59) showed dramatically increased risk (p < 0.05). In conclusion, rs1801394 in the MTRR gene is associated with gastric cancer risk, and its functional significance need to be validated.